Modeling Services Liberalization : The Case of Kenya - Balistreri, Edward J.; Rutherford, Thomas F.; Tarr, David G. (World Bank, Washington, DC, 2012)
This paper employs a 55 sector small open economy computable general equilibrium model of the Kenyan economy to assess the impact of the liberalization of regulatory barriers against foreign and domestic business service providers in Kenya. The model incorporates productivity effects in both goods and services markets endogenously, through a Dixit-Stiglitz framework. It estimates the ad valorem equivalent of barriers to foreign direct investment based on detailed questionnaires completed by specialists in Kenya. The authors estimate that Kenya will gain about 11 percent of the value of Kenyan consumption in the medium run (or about 10 percent of gross domestic product) from a full reform package that also includes uniform tariffs. The estimated gains increase to 77 percent of consumption in the long-run steady-state model, where the impact on the accumulation of capital from an improvement in the productivity of capital is taken into account. Decomposition exercises reveal that the largest gains to Kenya will derive from liberalization of costly regulatory barriers that are non-discriminatory in their impacts between Kenyan and multinational service providers.